2004
DOI: 10.1161/01.cir.0000145167.30987.2e
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Long Pentraxin PTX3 in Acute Myocardial Infarction

Abstract: Background-Inflammation has a pathogenetic role in acute myocardial infarction (MI). Pentraxin-3 (PTX3), a long pentraxin produced in response to inflammatory stimuli and highly expressed in the heart, was shown to peak in plasma Ϸ7 hours after MI. The aim of this study was to assess the prognostic value of PTX3 in MI compared with the best-known and clinically relevant biological markers. Methods and Results-In 724 patients with MI and ST elevation, PTX3, C-reactive protein (CRP), creatine kinase (CK), tropon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
328
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 409 publications
(364 citation statements)
references
References 45 publications
26
328
0
7
Order By: Relevance
“…In addition, the same study demonstrated that acute cardiac events were more common in patients with high PTX3 plasma concentration than in patients with normal PTX3 level [22]. PTX3 is also considered a good early marker of acute MI [23]. In our study, low baseline levels of PTX3 were observed both in the omega-3 group and the placebo group.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, the same study demonstrated that acute cardiac events were more common in patients with high PTX3 plasma concentration than in patients with normal PTX3 level [22]. PTX3 is also considered a good early marker of acute MI [23]. In our study, low baseline levels of PTX3 were observed both in the omega-3 group and the placebo group.…”
Section: Discussionsupporting
confidence: 67%
“…20 In addition, neutrophils contain a store of mature protein in their specific granules and can promptly release the molecule in response to proinflammatory signals. 21 Pentraxin is also expressed in cardiac tissue after MI, [17][18][19][20][21][22] and its plasma concentration predicts cardiovascular morbidity and mortality in patients with unstable angina, 23 MI, 24 or heart failure. 25 As expected, we found that patients admitted to a rehabilitation program after cardiac surgery presented with high concentrations of the biomarkers related to cardiac stress or injury (brain natriuretic peptide, cardiac troponin-T, creatine kinase, and myoglobin), generalized inflammation and vascular injury (C-reactive protein and pentraxin-3), and early renal glomerular dysfunction (albumin urinary excretion), but the marked decrease in biomarker levels during rehabilitation supports the global effectiveness of even short-term programs.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble RAGE (sRAGE), an extracellular domain of RAGE, was measured in duplicate in plasma and BALf samples (detection limit 4 pg/ml) using a specific enzymelinked immunosorbent assay (ELISA) (R&D Systems, Minneapolis, MN, USA) according to the manufacturer's protocols. PTX3 was assayed in duplicate by sandwich ELISA (detection limit 0.1 ng/ml), as previously described (Latini et al 2004). ELISA for PTX3 does not cross-react with CRP.…”
Section: Collection and Analysis Of Bronchoalveolar Lavage Fluidmentioning
confidence: 99%